Comparison of Energy Sources for an Electric Powertrain in a Tilt-Rotor Urban Air Mobility Vehicle - Jonas Ludowicy; Patrick Ratei; Stefanie de Graaf (Engineering Proceedings, 2025)
Electric vertical take-off and landing vehicles introduce challenges in powertrain design with short but high peak loads and low-load phases over longer periods of time during wing-borne flight. In this paper, three powertrain topologies are analyzed for a tilt-rotor urban air mobility vehicle with an expected entry into service after 2030. The powertrains are studied on the level of preliminary sizing for the design mission of the vehicle. The three powertrain topologies studied and compared are battery-only, fuel cell-only and a hybrid of the two energy sources. Parameter studies on the gearbox transmission ratio, the design point of the fuel cell system as well as the degree of hybridization were carried out. The combination of fuel cell and battery was found to be most beneficial in terms of mass when the fuel cell is sized for slightly more than cruise power. In flight phases with higher power requirements, the batteries would provide the additional boost.